Mental Health and Labour Market outcomes : Evidence from European countries - Stehno, Dominik; Kalíšková, Klára; Cingl, Lubomír, 1984-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
How mental health affects the labour market outcomes is an important question for health and labour policy. However, reliable causal estimates are relatively in short supply, especially in Europe. In this thesis, I estimate the effect of depressive disorders on labour market outcomes, such as employment, duration of unemployment, getting into leadership positions, and yearly hours worked using various econometric techniques. I address the potential endogeneity with an instrumental variable approach. Furthermore, I used methods proposed by Lewbel (2012) and Oster (2019) as alternatives. I found significant effects for all the examined dependent variables. The only exception is yearly hours worked. The empirical results are consistent with the previous literature. Nevertheless, results vary depending on the method used.
Vedoucí práce: Klára Kalíšková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses